2019
DOI: 10.21608/zumj.2019.24855
|View full text |Cite
|
Sign up to set email alerts
|

Study of Peripheral Neuropathy in Children With Type 1 Diabetes Mellitus at Zagazig University Hospitals

Abstract: Background: Diabetic peripheral neuropathy (DPN) plays a key role in morbidity and mortality in patients with type 1 and type 2 diabetes mellitus. The study was designed to assess frequency of diabetic peripheral neuropathy among the diabetic children and to evaluate the role of nerve conduction study (NCS) in diagnosis of DPN in children with type 1diabetes mellitus in comparison to neurological examination. Subjects and methods: A cross sectional study was conducted in Pediatrics Department, Zagazig Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…On the other hand a study at Zagazig University Hospitals revealed that the frequency of neuropathy in children with T1DM was 42.5% (17/40) [27] . In addition, a study conducted by Moser and coworkers reported that of 151 youth with type I diabetes 1 1 % were diagnosed with diabetic peripheral neuropathy (DPN).…”
Section: Similarly the European Diabetes Prospectivementioning
confidence: 98%
“…On the other hand a study at Zagazig University Hospitals revealed that the frequency of neuropathy in children with T1DM was 42.5% (17/40) [27] . In addition, a study conducted by Moser and coworkers reported that of 151 youth with type I diabetes 1 1 % were diagnosed with diabetic peripheral neuropathy (DPN).…”
Section: Similarly the European Diabetes Prospectivementioning
confidence: 98%